The long case and its modifications: a literature review - Ponnamperuma, G.G.; Karunathilake, I.M.; McAleer, Sean; Davis, M.H. (My University, 2009)
CONTEXT This review provides a summary of the published literature on the suitability of the long case and its modifications for high-stakes assessment. METHODS Databases related to medicine were searched for articles published from 2000 to 2008, using the keywords ‘long case’, ‘clinical examinations’ and ‘clinical assessment’. Reference lists of review articles were hand-searched. Articles related to the objective structured clinical examination were eliminated. Researchbased articles with hard data were given more emphasis in this review than those based on opinion. RESULTS Eighteen articles were identified. The main disadvantage of the long case is its inability to sample the curriculum widely, resulting in low reliability. The main advantage of the long case is its ability to assess the candidate’s overall (holistic) approach to the patient. Modifications to the long case attempt to: structure the format and the marking scheme; increase the number of examiners; observe the candidate’s behaviour, and increase the number of cases. CONCLUSIONS The long case is a traditional clinical examination format for the assessment of clinical competence and assessment at this level is important. The starting point for the majority of recent research on the long case has been an acceptance of its low reliability and modifications to the format have been proposed. Further evidence of the efficacy of these modifications is required, however, before they can be recommended for summative assessment. If further research is to be undertaken on the long case, it should focus on finding practicable ways of sampling the curriculum widely to increase reliability while maintaining the holistic approach towards the patient, which represents the attraction of the long case.